Dampak judi terhadap perilaku anakâ (Studi Kasus:Anak keluarga Penjudi di Korong Piliang Nagari Siguntur Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan) - Septria, Deka; Adiyalmon, Adiyalmon; Fitlayeni, Rinel (Pendidikan Sosiologi, 2014)
This study found a habit of leaving her husband in Nagari Siguntur the gamble. Average spend 8 hours / day to gamble, the husband s habit is indirectly an impact on families, especially children, the problem is not the functioning of the father in a family. This study wanted to see the impact of gambling on childrens behavior, while the purpose of the study to identify and reveal the impact of gambling on childrens behavior ( A case study in Korong Piliang gambler children in Nagari Koto XI Tarusan Siguntur District of Southern Coastal District ).The theory is used to study the structural functional theory proposed by Talcott Parsons. The method used in this research is descriptive qualitative approach. Informants numbered 7 family of gamblers, family gambler, gamblers and children who can explain the impact of gambling on childrens behavior. Informant selection techniques that researchers do is purposive sampling. Data collection methods such as interviews, observation and study dokumtasi. The data analysis technique used is to model the interactive analysis by Miles and Huberman, namely data analysis activities carried out continuously until the data is completely and finally saturated.The results of this study revealed that the impact of the father s behavior toward his gambler is 1 ) the behavior and properties both in children is a. Disrespectful way of speaking, b. Scrappy, 2 ) the emergence of a slacker nature in children, 3 ) like to gamble, 4 ) unruly.